ANALISIS LITERATUR TENTANG EFEKTIVITAS PROJECT BASED LEARNING BERDASARKAN PENELITIAN EKSPERIMEN TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SD - Setyowati, Mahira Intan; Nathania, Naddya; Amelia Kurnia Aji, Rizki; Ilmita Putri, Dona; Andhika Lusiana, Erny; Andriningrum, Hana; Indrawati, Delia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Critical thinking skills are among the skills elementary school students need to prepare them for the challenges of modern learning. However, classroom learning is still largely teacher-focused, leaving students with limited opportunity for in-depth thinking. Project-Based Learning (PjBL) is one learning model that can be implemented to address this issue by engaging students in project-based activities. This study aims to determine the effectiveness of implementing Project-Based Learning, based on experimental research findings, on critical thinking skills. The method used in this study was a literature review by examining various relevant scientific sources. The results indicate that implementing Project-Based Learning can improve students' critical thinking skills, particularly in analyzing problems, finding solutions, and disseminating work results. Therefore, this model can be an effective alternative for implementation in elementary school learning.